Penile Cancer Diagnosis and Treatment - Spiess, Philippe E.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Humana Press, 2017)
This fully updated and revised second edition address specifically some of the significant advances made in our understanding of the pathophysiology of penile cancer including discussion of the suspected role of the human papilloma virus in penile carcinogenesis. Similarly, the molecular pathways implicated in precancerous and penile cancer will be discussed as these are the present targets of novel therapeutic approaches to this disease. The text details the recent national and international diagnostic and treatment guidelines that have been developed by both the National Comprehensive Cancer Network© and the European Urological Association establishing evidence based standards upon which the care of penile cancer should be based. The text also covers significant advances made in the diagnostic and therapeutic approach to both primary tumors and inguinal nodal metastases resulting from penile cancer such as penile sparing surgery and minimally invasive inguinal lymph node surgery. The text will similarly highlights the improvement in cancer specific outcome in the management of loco-regionally advanced (N2/3) penile cancer managed by upfront systemic chemotherapy followed by consolidative surgery in appropriately selected patients based on recent prospective phase II data. It also covers the role of radiotherapy in the management of penile cancer for both primary tumors and/or at sites of regional or distant metastases. Finally, some of the novel systemic approaches being devised in the management of advanced penile cancer along with some upcoming international trials soon to be opened which likely will re-define the present therapeutic approaches to penile cancer are discussed. The Second Edition of Penile Cancer: Diagnosis and Treatment will constitute a comprehensive review of the above mentioned subjects in addition to a few select topics of high clinical relevance, with the readership predominantly consisting of urologists, medical and surgical oncologists, and other healthcare professionals.
Understanding the Pathophysiology of Penile Cancer and Its Preneoplastic Lesions -- Diagnostic Tools in the Evaluation and Management of Penile Cancer -- Penile-Sparing Surgical Approaches in the Management of Primary Penile Tumours -- Dynamic Sentinel Node Biopsy and FDG-PET/CT for Lymph Node Staging in Penile Cancer -- Surgical Decision Making, Technical Considerations and Clinical Pearls in Therapeutic Inguinal Node Dissection Surgery for Penile Cancer -- Minimally Invasive Surgical Approaches to Inguinal Nodes in the Absence of Palpable Adenopathy -- Pelvic Lymph Node Dissection for Penile Cancer: Answering the Conundrum of When and How It Should Be Conducted -- Multmodal Approach to Locally Advanced and Metastatic Penile Cancer -- The Role of Radiotherapy in the Management of Penile Cancer.
Keywords: Medicine; Oncology; Surgical oncology; Urology; Medicine & Public Health; Urology; Oncology; Surgical oncology